Institutional Development of Martial Arts and Combat Sports in Poland - Cynarski, Wojciech J. (International Martial Arts and Culture Journal, 2024)
Background and Aim. The development of martial arts is accompanied by their institutionalization, supported by the theoretical perspective of the General Theory of Fighting Arts (GTFA) and the sociology of physical culture. This study aims to examine the institutionalization process of fighting arts organizations using an institutionalization indicator (WI) based on the duration of organizational operation.Methods. This study employs qualitative research methods, including long-term participant observation and broad discourse analysis, to explore the development and institutional maturity of fighting arts organizations.Results. The findings indicate that the duration of operation significantly influences the position and institutional maturity of an organization, as well as its impact on the social environment. Long-term operation contributes to organizational stability and recognition within the community. A minimum period of 30 years of continuous activity is identified as an appropriate benchmark for achieving institutional maturity (WI = 1).Conclusion. Combat sports organizations of European origin and those associated with Olympic disciplines, such as judo, demonstrate the highest level of institutional maturity in Poland. Other fighting arts organizations tend to follow and adapt institutional patterns established by these more established organizations.